HbA1c as a predictor of diabetes after gestational diabetes mellitus. Issue 1 (February 2017) - Claesson, Rickard; Ignell, Claes; Shaat, Nael; Berntorp, Kerstin
Highlights: Third-trimester HbA1c was investigated as a predictor of diabetes following GDM. After five years, 73/196 (37%) of the women had developed diabetes. HbA1c ≥36 mmol/mol (≥5.4%) was associated with a 5.5-fold increased risk of diabetes. HbA1c showed high specificity but low sensitivity to predict diabetes post-partum. HbA1c could be used as a means of selecting high-risk women for interventions. Abstract: Aim: We wanted to investigate third-trimester HbA1c as a predictor of diabetes after gestational diabetes mellitus (GDM). Methods: Women with GDM were followed up prospectively for five years from pregnancy to detect the development of diabetes. The ability of HbA1c to predict diabetes was evaluated with receiver-operating characteristic (ROC) curves and logistic regression analysis. Results: By five years, 73 of 196 women had been diagnosed with diabetes. An optimal cut-off point for HbA1c of 36 mmol/mol (5.4%) could predict diabetes with 45% sensitivity and 92% specificity. For HbA1c ≥39 mmol/mol (≥5.7%), sensitivity, specificity, and positive predictive value were 30%, 97%, and 91%, respectively. In logistic regression analysis, adjusting for the diagnostic glucose concentration during pregnancy, HbA1c levels in the upper quartile (≥36 mmol/mol) were associated with a 5.5-fold increased risk of diabetes. Conclusion: Third-trimester HbA1c levels in the pre-diabetes range revealed women with post-partum diabetes with high specificity and high positive predictive value. HbA1c testing could be used as a strategy to select high-risk women for lifestyle interventions aimed at prevention of diabetes starting during pregnancy. The results should encourage further validation in other populations using new diagnostic criteria for GDM.